Geographic patterns of inversion polymorphism in the second chromosome of the cactophilic drosophila buzzatii from Northeastern Argentina - Soto, I.M. (2010)
The inversion polymorphisms of the cactophilic Drosophila buzzatti Patterson and Wheeler (Diptera: Drosophilidae) were studied in new areas of its distribution in Argentina. A total of thirty-eight natural populations, including 29 from previous studies, were analyzed using multiple regression analyses. The results showed that about 23% of total variation was accounted for by a multiple regression model in which only altitude contributed significantly to population variation, despite the fact that latitude and longitude were also included in the model. Also, inversion frequencies exhibited significant associations with mean annual temperature, precipitation, and atmospheric pressure. In addition, expected heterozygosity exhibited a negative association with temperature and precipitation and a positive association with atmospheric pressure. The close similarity of the patterns detected in this larger dataset to previous reports is an indication of the stability of the clines. Also, the concurrence of the clines detected in Argentina with those reported for colonizing populations of Australia suggests the involvement of natural selection as the main mechanism shaping inversion frequencies in D. buzzatii.